Self-assembly of Fe2O3 nanorods in carbon nanotube network as a 3D aerogel architecture for lithium ion batteries. Issue 5 (1st April 2019) - Lv, Xiaowei; Zheng, Pin; Wu, Zhuangchun; Yu, Jiashuo; Ge, Dengteng; Yang, Lili
Abstract: Self-assembly of nanosized materials has been extensively studied for the assemblies usually exhibit novel properties and show potential applications in many fields. However, there are few studies about the self-assembly behavior during the formation of 3D architectures. Herein, interesting self-assembly of ultrathin α -Fe2 O3 nanorods into micrometer-scale flakes or rods is exhibited during the formation of single walled carbon nanotube hydrogel network. The results show that this self-assembly is driven by oriented attachment mechanism with the assistance of surfactant acting as a template and 3D hydrogel structure as confined space. Benefitting from the 3D porous and interpenetrated structure, improved electron transfer network and increased active facets of Fe2 O3, an initial charge capacity is high as 891 mAh/g and 73% could be retained after 200 cycles. While great rate capability (42% preserved at 1000 mA/g) are also demonstrating its potential for applications in lithium ion batteries.